PERAN PEMERINTAHAN DESA PADA PENGEMBANGAN OBJEK PARIWISATA BANUA WUHU DI DESA MAHENGETANG - RADING, GRACE; KIYAI, BURHANUDDIN; TAMPI, GUSTAAF BUDDY (JURNAL ADMINISTRASI PUBLIK, 2019)
Based on the government regulation of the republic of Indonesia no 72 of 2005 concerning article 15, thevillage government is obliged to manage village potential in order to achieve the objectives of layingauthority in the implementation of village autonomy, these objectives include improving people’s welfare,equity and justice, democracy and respect for culture local, paying attention to the potential and diversity ofthe region. The aim of the research is to describe the role of the village government in the development ofmahangetang island tourism object. The focus of the research in the study is on four aspects, namely : 1).(attraction), 2) (accessibility), 3). (facility), 4) (institutional.Keyword : Role of village government, tourism.